IgG anti-RBD levels during 8-month follow-up post-vaccination with BNT162b2 and mRNA-1273 vaccines in healthcare workers: A one-center study - Gil-Manso, Sergio; Alonso, Roberto; Catalán, Pilar; Sánchez-Arcilla, Ignacio; Marzola, Marco; Correa-Rocha, Rafael; Pion, Marjorie; Muñoz, Patricia, Gregorio Marañón Microbiology-ID COVID-19 Study Group; Alcalá, Luis; Aldámiz, Teresa; Alonso, Roberto; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Since the COVID-19 outbreak, specific mRNA-based vaccines anti-SARS-CoV-2 have been developed and distributed worldwide. Because mRNA vaccines have been used for the first time against COVID-19, there are several questions regarding their capacity to confer immunity and the durability of the specific anti-SARS-CoV-2 response. Therefore, the objective of this study was to recruit a large cohort of healthcare workers of the Gregorio Marañón Hospital vaccinated with mRNA-1273 or BNT126b2 vaccines and to follow up the IgG Anti-S levels for 8 months post-vaccination. We recruited 4,970 volunteers and measured IgG Anti-S antibodies on days 30 and 240 post-vaccination. We observed that both vaccines induced high levels on day 30, and drastic wane was observed on day 240, with mRNA-1273 being the vaccine that induced higher levels compared to BNT162b2. Stratifying by vaccine type, age, and gender, we identified that older mRNA-1273 vaccinated volunteers had higher antibody levels compared to younger ones, contrary to what is happening in BNT162b2 volunteers. In conclusion, we observed that mRNA-1273 has a higher capacity to induce a humoral response than BNT162b2, and that, at least, age is a factor implicated in the specific response.